webCEMiTool: Co-expression Modular Analysis Made Easy - Cardozo, Lucas E.; Russo, Pedro S. T.; Gomes-Correia, Bruno; Araujo-Pereira, Mariana; Sepúlveda-Hermosilla, Gonzalo; Maracaja-Coutinho, Vinicius; Nakaya, Helder I. (Frontiers in Genetics, 2019)
Co-expression analysis has been widely used to elucidate the functional architecture of genes under different biological processes. Such analysis, however, requires substantial knowledge about programming languages and/or bioinformatics skills. We present webCEMiTool (https://cemitool.sysbio.tools/), a unique online tool that performs comprehensive modular analyses in a fully automated manner. The webCEMiTool not only identifies co-expression gene modules, but it also performs several functional analyses on them. In addition, webCEMiTool integrates transcriptomic data with interactome information (i.e. protein-protein interactions), and identifies potential hubs on each network. The tool generates user-friendly html reports that allow users to search for specific genes in each module, as well as check if a module contains genes over-represented in specific pathways or altered in a specific sample phenotype. We used webCEMiTool to perform a modular analysis of single-cell RNA-seq data of human cells infected with either Zika virus or Dengue virus.